1993
DOI: 10.1524/ract.1993.62.12.65
|View full text |Cite
|
Sign up to set email alerts
|

Fast Radiochemical Separation and γ Spectroscopy of Short-lived Thallium Isotopes

Abstract: A method for continuous separation and measurements of shortlived thallium isotopes is described. The Bi parent nuclides were fixed as anionic complexes B1CI4 on a Dowex 1-X8 column and the daughters Tl + were continuously eluted with a reducing solution and fixed on a Ni hexacyanoferrate(II)ion exchanger column, y-spectra of radiochemically separated 209 T1 (T ll2 = 2.2 min) and 208 T1 (T 1/2 = 3.05 min) nuclides were recorded with high efficiency HPGe coaxial detectors. Eleven y-transitions were measured in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The 225 Ac can be separated from 225 Ra with Dowex 50W-X8 cation exchange resin [13,14], however, this chromatography is inconveniently performed at 60 °C or 80°C. Also, we found the yield of 225 Ac by this method to be relatively poor.…”
Section: Resultsmentioning
confidence: 99%
“…The 225 Ac can be separated from 225 Ra with Dowex 50W-X8 cation exchange resin [13,14], however, this chromatography is inconveniently performed at 60 °C or 80°C. Also, we found the yield of 225 Ac by this method to be relatively poor.…”
Section: Resultsmentioning
confidence: 99%
“…High crosslinking degrees typically have a better stability towards radiation. 36,48,134 Dowex 50W-X8, a spherical-shaped strong cation exchange resin used in direct generators, has been reported by Samad et al and Geerlings et al 26,118 In these studies, 225 Ac (in a 1 M HNO 3 or 2 M HCl solution) was adsorbed onto the Dowex 50W-X8 column, while 213 Bi was eluted as BiCi 4…”
Section: Cation Exchange Sorbents With Sulfonic Acid Groupsmentioning
confidence: 89%
“…38,111 For example, Ac 3+ ions are adsorbed onto the cation exchange resin by cation exchange, while the Bi-halide complexes are adsorbed onto the anion exchange resins via the anion exchange. 26,38,111,118 Surface complexation is a crucial adsorption mechanism involving inner-and outer-sphere complexation (Fig. 7c).…”
Section: Adsorption Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…evaluated this generator using lower acid molarity for improved compatibility with antibody labeling, which resulted in decreased 213 Bi yield . El Samad et al also reported use of a similar 213 Bi/ 225 Ac generator, but with the 225 Ac initially extracted from 233 U by two strong anion-exchange columns (Dowex 1X8). Since their objective was a study of 209 Tl, only low-level generators were described.…”
Section: Sources and Generators For 213bimentioning
confidence: 99%